The ANALYSIS OF HATE SPEECH IN THE COMMENT COLUMN OF TIKTOK ACCOUNT: A FORENSIC LINGUISTIC STUDY - Wahidah Nasution; Farah Adilla (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
Social media has provided a space for freedom of opinion to all its users. However, this has caused not only positive impacts but also negative impacts. One of the negative impacts of communicating on social media is to harm some people or certain parties such as hate speech. This study aims to analyze the forms of hate speech of Indonesian netizens in Ganjar Pranowo's Instagram comment column which is analyzed using forensic linguistic analysis. The formulation of the problem in this study is how to analyze the forms of hate speech in the comment column of Ganjar Pranowo's tiktok account using forensic linguistic studies. The research design used in this study is descriptive research and data collection is carried out from the results of observation and analysis of language crimes. Data was collected from March 1-10, 2024. The data in this study is in the form of words and sentences of Indonesian netizens which are hate speech and thrown at Ganjar Pranowo in the Tiktok comment column. The data in this study is in the form of Tiktok social media that can be accessed by all parties, in the form of text taken through online searches in the Tiktok comment column of ganjarpranowo. The results obtained in this study are that the forms of hate speech are divided into 4 forms, namely insults, defamation, anger and annoyance, and hoaxes (fake news). The data obtained included insult there were 11 data, defamation there was 2 data, then anger and annoyance there were 3 data and hoax (fake news) there was 2 data. Insults are the most common and dominant hate speech. In general, hate speech contained on Ganjar Pranowo's tiktok account is dimensioned as an act of satire accompanied by bad ridicule with harsh and negative words and blasphemy that tends to lower the value, degrade and also accuse of committing an act.